ANTIBACTERIAL ACTIVITY OF CHLOROFORM EXTRACT AND RHIZOPHORA SPP LEAVES METHANOL EXTRACT ON MOUTH BACTERIA - Carolin Manuahe; Herry Sumampouw; Friska Montolalu (Indonesian Biodiversity Journal, 2021)
The purpose of this study was to obtain the phytochemical profile of the methanol and chloroform extracts of the leaves of Rhizophora apiculata and to find the antibacterial activity of the methanol and chloroform extracts against human oral bacteria. This research was carried out in 3 stages, namely Rhizopora spp. Leaf Sampling, Extraction and Analysis of Secondary Metabolite Content and Antibacterial Activity Test using the agar diffusion method. Based on the results of the phytochemical screening examination of the leaf extract of Rhizopora spp., the results showed that it was rich in chemical compounds of alkaloids, flavonoids, tannins, and saponins in both methanol extract and chloroform extract. The results of the antibacterial activity test of methanol extract obtained that the smallest concentration in bacterial isolate bacteria 2 was 30 mg/ml, while the smallest concentration in bacterial isolate 1 was 50 mg/ml. The results of the antibacterial activity test of the chloroform extract obtained that the smallest concentration in the bacterial isolate bacteria 2 was 20 mg/ml while the smallest concentration in the bacterial isolate 1 was 30 mg/ml. Both methanol extract and chloroform extract had better activity on gram-positive bacteria.